Telaah Kritis atas Pemikiran Zakaria Ouzon - Farid Hasan (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
This research aims to analyze and critically examine the idea of Zakaria Ouzon in his book Jinayah al-Bukhari. This study becomes relevant in the study of contemporary hadith. Although shaheeh Bukhari is considered as asahhu al-kutub ba’da alqur’an, but in reality there are some redactions needed to be clarified of the truth that can result proportionate and consistent understanding aligned with the message of Prophet Muhammad SAW as the best figure. From this research, it is found that Ouzon criticized the book of shaheeh bukhori related to the following matters: the history of Al-Bukhari related to al-Qur'an al-Karim, the figure of Prophet Muhammad SAW, the religions besides Islam, the law and conditions of Prophet’s companions, the women, the figure of Bukhari, and the hadiths which contradict each other. The approach implemented by Ouzon in his book includes three fully integrated components, namely a historical approach, logic, and comparison. However Ouzon’s arguments are sometimes polemically and tend to impose his arguments, as Ouzon’s assumption to hadiths that contradict science.